Routledge handbook of family law and policy - Eekelaar, John, 1942-; George, Robert H. 1984- (Routledge handbooks, 2021)
"This book considers the difficulties family law is attempting to cope with within jurisdictions, focusing on the key contemporary policy challenges facing family law. The specially written chapters draw on empirical research from the social sciences and demography to demonstrate how these issues are affecting family policy and uses this evidence to draw conclusions about the ways in which family law may develop in the future. Featuring contributions from a range of renowned global experts, the book does not limit itself to dealing with one jurisdiction but offers comparative analysis looking at circumstances in a range of countries"--